The degree of the employment of the educational technology in the educational process in the schools of kasabah AL Mafraq from the principal’s perspective - Al-Badi, Rogayah Awwad (Journal of Educational and Psychological Sciences, 2020)
The aim of the study was to identify the degree of the employment of the educational technology in the educational process in the schools of kasabah AL Mafraq from the principals perspective, To achieve this study, the descriptive approach was used, where a questionnaire was developed, consisting of three areas (school, teacher, and curriculum) with 21 paragraphs, and its validity and stability was verified, and then it was distributed on the sample of the study which was consisted of (146) principals in the schools of kasabat AL Mafraq. The result of the study showed that the degree of the employment of the educational technology in the educational process in the schools of kasabah AL Mafraq from the principals perspective was middle and with an average arithmetic (2.78). The results also showed no significant differences in the evaluations of the study’s sample members for the degree of the employment of the educational technology in the educational process in the schools of kasabah AL Mafraq from the principals perspective according to the gender variables and the Experience. In the light of the results, the researcher researchers recommended that the ministry of Education, should hold more specialized training courses and workshops, in the field of educational technology, and improve the technological infrastructure of schools.